Intermediate-term outcomes of laparoscopic pectopexy and vaginal sacrospinous fixation: a comparative study - Astepe, Bahar Sariibrahim (Int Braz J Urol, 2019)
OBJECTIVE: To compare the intermediate-term follow-up results of laparoscopic pectopexy and vaginal sacrospinous fixation procedures. MATERIALS AND METHODS: Forty-three women who had vaginal sacrospinous fixations(SSF) using Dr. Aksakal’s Desta suture carrier and 36 women who had laparoscopic pectopexies were re-examined 7 to 43 months after surgery. The PISQ-12 and P-QOL questionnaires were answered by all of the women. RESULTS: The apical descensus relapse rates did not differ between the groups (14% in the SSF vs. 11.1% in the pectopexy group). The de novo cystocele rates were higher in the SSF group (25.6% in the SSF vs. 8.3% in the pectopexy group). There were no significant differences in the de novo rectocele numbers between the groups. The treatment satisfaction rates were high in both groups (93% in the SSF vs. 91.7% in the pectopexy group), which was not statistically significant. Moreover, the postoperative de novo urge and stress urinary incontinence rates did not differ; however, the postoperative sexual function scores (PISQ-12) (36.86±3.15 in the SSF group vs. 38.21±5.69 in the pectopexy group) were better in the pectopexy group. The general P-QOL scores were not significantly different between the surgery groups. CONCLUSION: The vaginal sacrospinous fixation maintains its value in prolapse surgery with the increasing importance of native tissue repair. The new laparoscopic pectopexy technique has comparable positive follow-up results with the conventional sacrospinous fixation procedure.